Assessment of Agreement between Gated SPECT Myocardial Perfusion Imaging and Gated SPECT Blood Pool Imaging for Measurement of Left Ventricular Ejection Fraction in Coronary Artery Disease - Sarker, Azmal K; Hussain, Raihan; Nasreen, Faria; Nisa, Lutfun; Hoq, Monsurul; Nath, Khokon K; Khatun, Nurjahan; Islam, Saiful; Alam, Faridul (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Quantitative assessment of left ventricular ejection fraction (LVEF) from radionuclide cardiac imaging study has both diagnostic and prognostic value in coronary artery disease (CAD). Gated SPECT blood pool imaging (GSBPI) and gated SPECT myocardial perfusion imaging (GSMPI) are two technically comparable radionuclide methods for non-invasive measurement of LVEF. While the former is a gold standard the latter is popular as it provides a wider array of information. This study was carried out to bridge the lack in the existing body of evidence regarding assessment of agreement of between GSBPI and GSMPI for measurement of LVEF in CAD. The objective of this study is to validate the LVEF measurements from routine GSMPI as a valuable parameter for clinical decision making through assessment of agreement between GSMPI and GSBPI performed in a short interval, in same patient having CAD. Patients and Methods: A total of 28 patients (three female) was observed with a mean age of 54.5 ± 8.5 years during February to May 2012. All patients underwent GSBPI and GSMPI with a gap of three to seven days in between. LVEF measured by GSBPI performed at rest was compared with LVEF measured in rest phase of one day stress-rest GSMPI. Agreement analysis was done with Bland Altman plot. Results: Mean LVEF measurements show an apparent overall slight underestimation by GSBPI (54.8.9±25) in comparison to GSMPI (56.9±25). Bland Altman plots show that the differences between GSBPI and GSMPI for measurement of LVEF at rest in same patient fall within two SD of the mean difference. This finding remained similar while further categorization of study patients was done on basis of ranges of LVEF, end diastolic volume (EDV), end systolic volume (ESV), infarct size and regional wall motion abnormality (RWMA). Conclusions: There was overall significant agreement between GSMPI and GSBPI for measurement of LVEF in CAD in this small study. This agreement remains significant irrespective of ranges of LVEF, EDV, ESV, infarct size and RWMA. Bangladesh J. Nuclear Med. 19(2): 128-134, July 2016